The pathomechanism of bone marrow edema in the femoral head necrosis with pericollapse stage - Liang Mo; Zhangzheng Wang; Mengyu Jiang; Chi Zhou; Chao Ma; Yinuo Fan; Wei He; Zhenqiu Chen; Yuhao Liu (Scientific Reports)
Abstract Bone marrow edema (BME), a notable manifestation during the progression of osteonecrosis of the femoral head (ONFH), exhibits significant associations with femoral head collapse, pain, and prognosis, howeverits’ pathogenesis remains underexplored. In this study, specimens from patients undergoing total hip arthroplasty (THA) were analyzed. The results revealed significantly higher Visual Analog Scale (VAS) scores and CT low-density area ratio in the BME group compared to the control group. Furthermore, Sirius Red staining exhibited fibrotic tissue in both necrotic and sclerotic areas, with more pronounced effects in the BME group. Meanwhile, data-independent Acquisition (DIA) proteomics technology was utilized to identify differentially expressed proteins (DEPs) within bone tissue. 141, 299 and 852 DEPs were identified in femoral neck, necrotic and sclerotic regions, respectively. Immune responses, inflammatory reactions and oxidative stress were markedly altered in ONFH cases with BME. In bone tissue, the levels of malondialdehyde (MDA) and proteins associated with osteoclast activity were found to be elevated in the BME group. In conclusion, BME in ONFH at pericollapse stage is associated with inflammation, fibrosis, heightened oxidative stress and increased osteoclast activity. These factors collectively elevated the risk of collapse or re-collapse. Targeted interventions aimed at neutralizing these risk factors show potential in slowing down the progression of the disease.